Friendly Jamming on Access Points: Analysis and Real-World Measurements - Berger, Daniel S.; Gringoli, Francesco; Facchi, Nicolò; Martinovic, Ivan; Schmitt, Jens (IEEE Transactions on Wireless Communications, 2016)
Frequency jamming is known as an efficient attack tool to disrupt wireless communication. This efficiency can also be exploited for the benefit of a network—an idea often referred to as friendly jamming. A prominent application case is the blocking of unauthenticated or malicious communication, such as injection attacks. In this paper, we propose access points as a natural place to implement friendly jamming functionality. We analyze this proposal using simulations, introduce an implementation on customer-grade access points, and report measurement results from the first real-world study of friendly jamming in an IEEE 802.11 campus network. We discover a fundamental tradeoff between the effectiveness of friendly jamming and the orthogonal aspect of having minimal side-effects to the campus network’s traffic. In particular, we observed what we call the power amplification phenomenon. This effect aggravates the known hidden station problem when the number of jammers increases. We also find evidence that the collaboration between jammers can enable friendly jamming, which is both effective and minimally invasive.